Pemanfaatan Aplikasi Quizizz dalam Meningkatkan Antusiasme Peserta Didik - Chrisvia, Mildza; Millah, Fidaiyatul; Febrianti, Ericka; Havidah, Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This research aims to determine the increase in students' enthusiasm in using the Quizizz application in learning Islamic Cultural History (SKI). The research was carried out on students at Raden Fatah High School in the odd semester of the 2024-2025 academic year. The research method used was descriptive research using a quantitative approach, sampling was carried out using saturated sampling. The results of the analysis show that students' understanding in using the Quizizz application is 76%, and from the results of this analysis it can be concluded that learning using the Quizizz application can influence students' enthusiasm for learning in the Islamic Cultural History (SKI) subject.